Academia and industry collaboration: It takes two (+1) to tango! - Chen L.F.; Omar R. (2023)
Malaysia's aspiration is to be a developed nation by the year 2020. This sacred aspiration aptly known as the "Wawasan 2020" requires the amalgamated effort of three important parties: university, industry and government. Universities not only have an important role as " producers" of this highly intensive knowledge-based society which contributes to human capital building, but they are also in the driving seat of Research, Development and Innovation (RD&I). Throughout the years, various models of this joint venture between these three entities have been proposed. This paper will look into various factors supporting this venture, the potential pitfalls to be avoided and experiences of successful ventures. 2011 IEEE.